Actividades lúdicas a través de las TIC en la enseñanza-aprendizaje de matemática del sexto grado de la Unidad Educativa Marieta de Veintimilla - Salas Alejandro, Sandra Betty (2022)
Nowadays, playful activities in the teaching-learning process are very important, allowing to reinforce and strengthen what students have learned, as well as contributing to socialization, cooperation and sharing knowledge as a team, which strengthens meaningful learning; the main objective of this work was to propose a methodological guide with playful activities through ICT, which contribute to the teaching-learning process in the area of mathematics for the sixth grade of Basic Education of the Marieta de Veintimilla Educational Unit. The approach used was quantitative, with a transversal design in which the data were collected at a determined time and moment. The sample consisted of 101 sixth grade students and 18 teachers. In order to fulfill the objectives, bibliographic information was obtained in relation to the variables proposed and to give theoretical support to this work, then the questionnaire was applied as an instrument to obtain information and establish the importance of the use of the WordWall platform in the teaching-learning process and finally a methodology proposal was elaborated with each of the steps to be able to use this platform. The analytical-synthetic and inductive method was used, applying the survey technique through the questionnaire, managing to collect information on the needs of students and teachers to apply playful activities in the teaching-learning process. Within the results it was possible to evidence the need of students and teachers to know the platform to be able to apply it in the classes of the subject of Mathematics, being dynamic and fun, It is concluded that the WordWall platform has advantages for its use, since it is accessible for both teachers and students. Key words: Playful activities, Mathematics, WordWall, ICT, teaching-learning.